Effect of occupational lead exposure on α- and γ-tocopherol concentration in plasma - Prokopowicz, Adam; Sobczak, Andrzej; Szuła, Magdalena; Anczyk, Edmund; Kurek, Jolanta; Olszowy, Zofia; Radek, Małgorzata; Pawlas, Natalia; Ochota, Patryk; Szołtysek-Bołdys, Izabela (Occupational and environmental medicine (London, England), 2013)
Objectives Changes in enzymatic antioxidant activity are frequently observed in workers occupationally exposed to lead. Few studies have investigated the influence of lead on the non-enzymatic antioxidant system. The aim of our study was to assess the influence of occupational exposure to lead on the plasma concentration of two hydrophobic forms of vitamin E: α-tocopherol and γ-tocopherol. Methods A sample of 401 healthy men, aged 19–62, participated in the study. In total, 340 of these subjects were employed at the Mine and Metallurgical Plant in southern Poland. The workers who were occupationally exposed to lead were divided into quartiles (groups of 85 subjects). The lead concentrations in the blood of the subjects in the control group and in the lead exposure quartiles correspond to the following ranges: 10–72 μg/l (control group); 82–206 μg/l (Q1); 209–308 μg/l (Q2); 308–394 μg/l (Q3) and 395–644 μg/l (Q4), respectively. Results Significant differences were observed only for the plasma concentration of γ-tocopherol, which differed between the control group and Q1 (by 24.1%, p=0.0368), between Q1 and Q3 (by −18.8%, p=0.0115) and between Q1 and Q4 (by −25.7%, p=0.0002). Multiple linear regression analysis showed that the statistically significant, predictive properties of the γ-tocopherol plasma concentration were as follows: triglycerides (β=0.440)> age (β=0.131)> whole cholesterol (β=0.117)> blood lead concentration (β=−0.108). For α-tocopherol, significant prognostic properties were triglycerides and total cholesterol (β=0.485 and β=0.399, respectively). Conclusions Occupational exposure to lead is strongly correlated with the concentration of γ-tocopherol but not α-tocopherol.